CLIMACOPTERA LANATA (PALL.) BOTSCH. ЎСИМЛИГИНИНГ ГЕОГРАФИК ТАРҚАЛИШИГА ОИД МАЪЛУМОТЛАР - Ажиев, А.В.; Мамарахимов, О.М. (SCIENCE and SOCIETY, 2025)
This research paper presents the morphology, ecology and geographical distribution of the Climacoptera lanata (Pall.) Botsch. The map illustrating its distribution is created using the Google Earth Pro software.